Brazilian Jurisprudence in a Risk Society: The non-patrimonial or Moral environmental damage issue - Leite, José Rubens Morato; Venâncio, Marina Demaria (JURIS - Revista da Faculdade de Direito, 2016)
Environmental law in Post Industrial Society faces new challenges imposed by Risk Society. In this following, this paper aims to discuss how civil liability and non-patrimonial environmental damage are involved in new approaches for Brazilian judicial decision-making and concerning about environmental damage. In this study, the methodology used is descriptive in a bibliographic research. By this, it happens to comprehend the Brazilian Jurisprudence new views, in relation to risk society and civil liability. It is important to reflect about it, because the present is marked by the environmental crisis, and an improvement of decision-making mechanisms for a better juridical system are needed.